2015
DOI: 10.1108/jap-11-2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses on placement – collaborators or challengers

Abstract: Purpose – All nursing students have the opportunity to gain experience in the Independent Sector. The Health and Social Care Act (2012) in the UK has led to more health services being provided by the Independent Sector. The purpose of this paper is to explore the perceptions of first year student nurses of their learning experience in nursing homes placements within the Independent Sector. Design/methodology/approach – Two focus groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nursing students' experiences of working alongside RNs was highlighted throughout the literature. However, the results revealed that in reality, students spend a great deal of time working alongside health care assistants (HCA) in nursing homes and that this negatively impacts their placement experiences (Xiao et al, 2012;Annear et al, 2014;Clarke, 2015) and their ability to understand the role of nursing home RN (Moquin et al, 2018;Watson et al, 2020). This illustrates the priority that nursing students place on developing their professional identities through the process of socialisation alongside RNs in nursing homes (Neville et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing students' experiences of working alongside RNs was highlighted throughout the literature. However, the results revealed that in reality, students spend a great deal of time working alongside health care assistants (HCA) in nursing homes and that this negatively impacts their placement experiences (Xiao et al, 2012;Annear et al, 2014;Clarke, 2015) and their ability to understand the role of nursing home RN (Moquin et al, 2018;Watson et al, 2020). This illustrates the priority that nursing students place on developing their professional identities through the process of socialisation alongside RNs in nursing homes (Neville et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The studies reviewed indicated that some students were unclear about what RNs in nursing homes do (Skaalvik et al, 2012;Clarke, 2015;Moquin et al,2018) resulting in reduced confidence for achieving learning outcomes compared to an acute hospital placement (Indar et al, 2018;Watson et al, 2020). Clarke ( 2015…”
Section: Understanding the Roles Of Staff In Nursing Homesmentioning
confidence: 99%